In the following *s = v, z* or *s* depending on whether we have a Fourier transform,
*Z*-transform or a Laplace transform.

H(s) = |
Y(s) |
= |
Y(s) |
· |
Y(_{1}s) |
= H(_{1}s) H(_{2}s) |

X(s) |
Y(_{1}s) |
X(s) | ||||

H(s) = |
Y(s) |
= |
Y(_{1}s) + Y(_{2}s) |
= |
Y(_{1}s) |
+ |
Y(_{2}s) |
= H(_{1}s) + H(_{2}s) |

X(s) |
X(s) |
X(s) |
X(s) | |||||

X(_{1}s) = X(s) + Y(_{1}s) |

Y(_{1}s) = H(_{2}s) Y(s) |

Y(s) = H(_{1}s) X(_{1}s) |

H(s) = |
Y(s) |
= |
H(_{1}s) X(_{1}s) |
= |
H(_{1}s) X(s) + H(_{1}s) Y(_{1}s) |

X(s) |
X(s) |
X(s) | |||

= H(_{1}s) + |
H(_{1}s) H(_{2}s) Y(s) |
= H(_{1}s) + H(_{1}s) H(_{2}s) H(s) |

X(s) | ||

=> H(s) = |
H(_{1}s) |

1 - H(_{1}s) H(_{2}s) | |

Previous section

Next chapter

Contents